Time to achieve a patient acceptable symptom state in myasthenia gravis - Martinez-Harms, Rodrigo; Barnett, Carolina; Bril, Vera (Frontiers in Neurology, 2023)
Introduction The patient acceptable symptom state (PASS) is a reliable way to characterize a patient’s satisfaction with their disease state in a “Yes”/“No” dichotomous manner. There is limited data on the time required to reach an acceptable state in Myasthenia Gravis (MG). We aimed to determine the time to reach a first PASS “Yes” response in patients at MG diagnosis and a PASS “No” status, and also to determine the influence of various factors on this time. Methods We performed a retrospective study of patients diagnosed with myasthenia gravis who had an initial PASS “No” response and defined the time to reach a first PASS “Yes” by Kaplan–Meier analysis. Correlations were made between demographics, clinical characteristics, treatment and disease severity, using the Myasthenia Gravis Impairment Index (MGII) and Simple Single Question (SSQ). Results In 86 patients meeting inclusion criteria, the median time to PASS “Yes” was 15 months (95% CI 11–18). Of 67 MG patients who achieved PASS “Yes,” 61 (91%), achieved it by 25 months after diagnosis. Patients who required only prednisone therapy achieved PASS “Yes” in a shorter time with a median of 5.5 months (p = 0.01). Very-late-onset MG patients reached PASS “Yes” status in a shorter time (HR = 1.99, 95% CI 0.26–2.63; p = 0.001). Discussion Most patients reached PASS “Yes” by 25 months after diagnosis. MG patients who only required prednisone and those with very-late-onset MG reach PASS “Yes” in shorter intervals.